2020
DOI: 10.3758/s13423-020-01735-6
|View full text |Cite
|
Sign up to set email alerts
|

Ideomotor compatibility enables automatic response selection

Abstract: A task is ideomotor (IM)-compatible when there is high conceptual similarity between the stimulus and the associated response (e.g., pressing a left key when an arrow points to the left). For such an easy task, can response selection operate automatically, bypassing the attentional bottleneck that normally constrains dual-task performance? To address this question, we manipulated the IM compatibility of a Task 2 that was performed concurrently with a non-IM-compatible Task 1, using the psychological refractory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Interestingly, whereas the ability to automatize was negatively correlated with advancing age, it was uncorrelated with task speed. Third, both experiments replicated Maquestiaux et al’s (2020) findings that IM tasks can consistently be automatized and bypass the central bottleneck, at least for younger adults. Fourth, the results support the ORCA hypothesis, according to which older adults tend to strategically overapply central attention to novel tasks.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, whereas the ability to automatize was negatively correlated with advancing age, it was uncorrelated with task speed. Third, both experiments replicated Maquestiaux et al’s (2020) findings that IM tasks can consistently be automatized and bypass the central bottleneck, at least for younger adults. Fourth, the results support the ORCA hypothesis, according to which older adults tend to strategically overapply central attention to novel tasks.…”
Section: Discussionsupporting
confidence: 69%
“…An example would be saying the word you hear (known as shadowing ) or moving your finger to the location of a stimulus. Such easy tasks are automatic for younger adults (Maquestiaux et al, 2020), but might not be for older adults.…”
mentioning
confidence: 99%
“…As a result, parallel automatic T b (T 2 ) response activation might interfere with the response selection process of T p (T 1 ; e.g., Hommel, 1998; Janczyk et al., 2018; Thomson et al., 2015). Critically, it is not clear whether this response activation reflects parallel automatic motor activation or some kind of generic activation that is not related to motor cortex activity and could arise due to parallel automatic premotor response selection processes (e.g., Maquestiaux et al., 2020). It is also unclear whether the BCE should be attributed to premotor or motor processes within resource‐sharing models.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these speculations, other studies have found that dual-task processing also depends on task structure (e.g., ideomotor and stimulus-response compatibility, cf. Halvorson, Ebner, & Hazeltine, 2013; Lien et al, 2002, 2005; Maquestiaux et al, 2020), as well as on the cognitive control processes that coordinate the instructed task order (e.g., Kübler et al, 2022a, 2022b; Luria & Meiran, 2003; Steinhauser et al, 2021). Furthermore, motor-level interference might also be involved because there is evidence that initiating a T 1 response prevents initiating a T 2 response in close succession (Keele, 1973; Klapp et al, 2019; Ulrich et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One may speculate that the present T 2 performance advantage could be caused solely by reactive (i.e., online) changes in preparatory processes without assuming any sharing or reallocation of limited processing resources (i.e., resources that are required for actual task processing). Accordingly, even though participants only process one task at a time (i.e., with 100% of processing resources), they could be slower in retrieving the T 1 -specific than T 2 -specific S-R mappings from working memory at long SOA, because they initially prepared both T 1 and T 2 mappings (and potentially also the switch between these tasks) and after completing T 1 they can fully load up preparation for T 2 (for a similar suggestion, see Maquestiaux et al, 2020). In other words, participants may keep S-R mappings for both tasks active during T 1 processing, but afterward only the ones for T 2 .…”
Section: Methodsmentioning
confidence: 99%